The time administration and cost burden of intravenous immunoglobulin (IVIG) therapy in a 4-year-old girl with Kawasaki disease: A case report - Nenden Nursyamsi Agustina; Fitranto Arjadi (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Kawasaki disease (KD) is an acute systemic vasculitis frequently affecting children under five years old. KD can cause severe complications. It can lead to coronary aneurysms in 15-25% of untreated cases. Intravenous immunoglobulin (IVIG) treatment within ten days of initial onset can reduce the rate of coronary artery aneurysms. However, IVIG administration in Indonesia is currently limited due to its high cost. The case reported a 4-year-old girl with a chief complaint of fever. She complained about a high fever seven days before hospitalization. She also complained about vomiting, cough, joint pain, diarrhea, skin peeling, and rash on her body, palms, and soles. On examination, she looked irritable and sluggish. The temperature was 39.9o C. There were red eyes without discharge, strawberry tongue, oral thrush, and red, dry, cracked lips, swollen neck lymph nodes, and skin rash on her body, palms, and soles. Laboratory testing showed microcytic hypochromic anemia with Hb 7.9 g/dL and leukocytosis 24.230/mm3. Chest X-ray showed perihilar and paracardial infiltrates. Electrocardiogram revealed sinus tachycardia. An echocardiogram showed left ventricle dilatation with trivial mitral regurgitation and no coronary abnormalities were found. She was diagnosed with Kawasaki Disease. She was treated by IVIG 30 gr single dose during 12 hours on day 7 of initial onset, methylprednisolone injection 10 mg/8 hours, paracetamol 150 mg/8 hours, and aspirin 400 mg/8 hours orally and discharged from the hospital with improvement. There weren’t any coronary artery abnormalities found. IVIG administration within ten days of initial onset in KD patients can reduce the risk of coronary artery complications. IVIG administration after day 10 of initial onset can achieve resolution of inflammation but can be insufficient for preventing coronary artery lesions (CALs).